Un retrato del artículo vasco en el año 1895 mediante el programa "VDM" - Ekaitz Santazilia (Anuario del Seminario de Filología Vasca "Julio de Urquijo.", 2010)
In this paper we offer a concrete application of the computer program VDM, which, given the input of the late XIXth century Bourciez corpus, provides us with clear information about the geographical and functional distribution of the article in Basque at that time. After describing the advantages and defects of the method employed, we discuss a series of linguistic theories about the article, to see how they fit in with the new data provided. Furthermore, by means of this method, which provides data about the geographical distribution of the article, we offer valuable data to explain its progressive introduction into the Basque language. At the same time, we show how the diatopic, as well as the diachronic use of the determiner depends on the type of clause, making it possible to establish a hierarchy and a relative chronology.